Joint Search and Aggregate Fluctuations - Jochen Mankart; Rigas Oikonomou (Verein für Socialpolitik, 2010)
We develop a theory of incomplete markets where households that consist of two ex ante identical, and ex post heterogeneous agents can provide mutual insurance though adjustments in labor supply. We do so by taking stock from the vast literature of search models of the labor market and trace the differences between bachelor and couples household economies. Our main goal is to address whether joint search within the household unit can help reconcile the suggestive business cycle properties of aggregate employment, unemployment and labor force participation. We use data from the CPS on labor market transitions of married couples and we show that joint insurance is important factor in explaining why the labor force is nearly acyclical. When we turn to the model however we find that these predictions are not entirely consistent with our theory. We then go on to explore what important additions need to be made to our benchmark framework to bring the model closer to the data.
Keywords: E24; E32; D58; 330